Incidence and risk factors for development of hepatocellular carcinoma at young age in patients with chronic hepatitis B. (2nd January 2022) - Goh, Myung Ji; Kang, Wonseok; Kim, Kwang Min; Sinn, Dong Hyun; Gwak, Geum-Youn; Paik, Yong-Han; Choi, Moon Seok; Lee, Joon Hyeok; Koh, Kwang Cheol; Paik, Seung Woon
Abstract: Background: Some young adults with chronic hepatitis B virus (HBV) infection might be at high risk for hepatocellular carcinoma (HCC), enough to justify regular HCC surveillance despite the young age of the patients. However, ways to identify at-risk individuals who may benefit from HCC surveillance need further evaluations. Methods: A hospital-based retrospective cohort of 2757 chronic HBV mono-infected young adults (median age: 34 years, males 66%) were analyzed. The primary outcome was young-onset HCC, defined as a diagnosis made under 40 years of age. We calculated the HCC incidence/1000 person-years in the overall cohort and pre-defined subgroups of patients assessed the independent risk factors that can be used to identify surveillance targets. Results: The HCC incidence was low (2.55/1000 person-years) in the overall cohort. However, the HCC incidence varied widely according to baseline characteristics: lowest among young adults with FIB-4 ≤ 0.70 (0.17/1000 person-years) and highest in young adults with radiological cirrhosis (30.7/1000 person-years). In multivariable analysis, radiological cirrhosis, the FIB-4 index, and serum HBV DNA level were independent factors associated with HCC development at a young age. Performance for prediction of young-onset HCC in radiological cirrhotic patients showed the highest specificity but sensitivity was <70%. Combination with FIB-4 index and HBV DNA levels increased sensitivity to 90%. Conclusion: Risk stratification using FIB-4 index, HBV DNA levels, and either combining radiological cirrhosis or gender and AFP levels would be helpful to stratify young patients who would and would not benefit from regular HCC surveillance.